Wujud Rekonsiliasi dalam Kearifan Lokal Budaya Flores - Yulita C. Age, Maria (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This article aims to describe conclusions about several forms of local wisdom of Flores culture which are a description of customs and beliefs that are able to restore a situation or relationship to be good as before and describe the similarities and differences between these forms of reconciliation from a religious point of view. This study uses a qualitative approach. Data was collected by means of interviews, documentation, and observation. The results showed that there is local wisdom of Flores culture which is a form of reconciliation, namely wale, waja, and tala. These three things are an effort to restore a relationship in relation to traditional marriage. When viewed from a religious perspective, these three things have similarities and differences with the sacrament of penance. The similarities are seen in purpose, substitution, non-representation, and reconciliation. What distinguishes it is the form of execution/implementation, the person involved, the form of substitution, the method of recognition, and the intention